THE ROLE OF GOVERNMENT POLICY IN BOOSTING THE ISLAMIC MICROFINANCE INSTITUTIONS PERFORMANCE IN INDONESIA - Tasya Aspiranti; A. Harits Nu’man; Yudha Dwi Nugraha; Ima Amaliah; Ade Yunita Mafruhat (Univeristas Islam Bandung, 2021)
In building a successful Islamic Microfinance Institutions (IMFIs) performance, many factors must be considered based on a multi-element point of view. This study aims to build key factors affecting IMFIs performance using multi-perspective and multi-criteria methods. This study uses an analytic network process (ANP) to calculate the degree of influence given by the IMFIs performance criteria and factors. Primary and secondary data collection techniques are used to collect required data for this research. The primary data are collected through questionnaires and interviews. A purposive sampling technique to collect primary data is used to the 26 local BPRS, 11 BMT including on the islands of Java, Sumatra and Sulawesi as a three biggest island of Indonesia. The results of the study find, internal and external management aspects are two main problems affecting IMFIs and five main solutions to increase their financing are regulatory, management, institutions, competencies, and partnerships.